APPEARANCE OF NEW EXPORT FEATURES OF UKRAINIAN ENTERPRISES ON INTERNATIONAL COMPETITIVE MARKETS AS A STRATEGIC PRIORITY FOR FORMATION OF INNOVATIVE ECONOMY (INNOVATIVE ECONOMY, 2020)
Mnykh O.B., Sapotnitska N.Ya. APPEARANCE OF NEW EXPORT FEATURES OF UKRAINIAN ENTERPRISES ON INTERNATIONAL COMPETITIVE MARKETS AS A STRATEGIC PRIORITY FOR FORMATION OF INNOVATIVE ECONOMYPurpose. Investigation of the preconditions of effective competition as the driving force of business activity, the development of innovative activity of exporters in the conditions of globalization of business and expansion of the economic space of free trade zones.Methodology of research. The theoretical and methodological basis of the research is the scientific works of scientists and researchers, normative acts and laws of Ukraine which governing the formation of an innovative economy.In the course of the research, general scientific and special methods were used by the analysis of trends and strategies for the development of Ukrainian exports and imports of goods and services in the context of the expansion free trade zones.Findings. The tendencies of Ukrainian export and import of goods and services in the conditions of the expansion of free trade zones are described. Trends have been constructed to displaying the rate of change in export volumes and the correlation has been researched between the growth of exports and the change of Ukraine’s competitive position in world markets. It is determined that the activity of Ukrainian exporters correlates with the level of activity of business entrepreneurship in the country. The reasons for the low efficiency of the export policy of the state are established.Originality. Based on the theory of J. Schumpeter, a general content model is constructed that reflects the interconnections in the development of effective competition and business partnership in the new conditions of the international market environment and the expansion of free trade zones with Ukrainian goods.Practical value. The obtained results of the research represent the conditions for effective competition which are based on the combination of state regulation and instruments of the market mechanism, and reveal new directions of scientific research of innovative development and source of resource support for growth of export potential of innovative enterprises.Key words: competition; effective competition; export; import; export potential; innovations; market.
Keywords: Key words; competition; effective competition; export; import; export potential; innovations; market.